Synthesis of "graphene-like" mesoporous carbons for shape-stabilized phase change materials with high loading capacity and improved latent heat. Issue 46 (13th November 2017) - Wang, Jiawei; Jia, Xilai; Atinafu, Dimberu G.; Wang, Mingshuo; Wang, Ge; Lu, Yunfeng
Abstract : We report a facile method of preparing mesoporous carbons which were used as supporting frameworks for high-loading and high-enthalpy PCMs. Abstract : Mesoporous carbons with high porosity, large specific surface areas and a certain degree of graphitization were facilely prepared via carbonization of sucrose at different temperatures of 700 °C (C-700), 800 °C (C-800) and 900 °C (C-900) and were used as supporting frameworks for phase change materials (PCMs) loading paraffin. The as-prepared carbons had high loading capacity of paraffin as demonstrated by leakage tests. The paraffin loading capacity of C-700, C-800 and C-900 reached up to 88.8 wt%, 91.7 wt% and 90.6 wt% respectively without leakage, and the corresponding latent heats were 103.0%, 104.5% and 102.9% that of pure paraffin with the same actual paraffin amount, showing improved latent heat. TG results showed that the as-prepared PCMs had better thermal stability and their good thermal cycling stability was demonstrated by thermal cycling tests after 50 cycles. Furthermore, the thermal conductivity of the composite PCMs improved to a certain degree compared with that of pure paraffin.